Statistical Accounting Of Services Provided In The Territories And Statistical Assessment Of Their Impact On The Income Of The Population (Texas Journal of Multidisciplinary Studies, 2022)
This article statistically examines the specific features of the services provided and the impact of the volume of services provided in order to increase real per capita income in the regions.